Pengaruh Kompensasi, Motivasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan: - Kuyun Lindasari; Jajuk Herawati; Epsilandri Septyarini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to determine the effect of the independent variables, namely compensation, motivation, and work environment on the dependent variable, namely job satisfaction. This type of research is quantitative research. The population is all employees in Balai Diklat Industri Yogyakarta. The sample is 53 samples. The sampling technique used nonprobability technique (saturated sampling). The data collection method in this study is a questionnaire distributed to all employees Balai Diklat Industri Yogyakarta. The data analysis technique used multiple linear regression, t test (partial), f test (simultaneous), and coefficient of determination (R2). The results of this study indicate that compensation has no positive and significant effect on employee job satisfaction, motivation has a positive and insignificant effect on employee job satisfaction, work environment has a positive and significant effect on employee job satisfaction, and compensation, motivation and work environment have a simultaneous effect on job satisfaction. employee work. Keywords: Compensation, Motivation, Work Environment, Job Satisfaction